Improving channel availability of tree-topology-based IPTV networks with users zapping channels sequentially. (1st January 2014) - Lai, Junyu; Wolfinger, Bernd E.
In service provider-based internet protocol television (IPTV) systems, users' sequential zapping behaviour can introduce extra traffic load in transmission networks, which may greatly degrade user quality of experience (QoE). In this paper, we focus on improving TV channel availability (one most crucial QoE metric) in tree-topology-based IPTV networks with users zapping channels sequentially. Firstly, the impact of the sequential zapping behaviour on channel availability is illustrated by a comparative study. Subsequently, aiming to alleviate this impact, we propose an extended intentional switching delay (iSD) admission control method with a two-layered (base/enhancement layer) scalable video coding (SVC) profile for tree-topology-based IPTV networks. Comprehensive simulation experiments are carried out and show that, in both peak-hour and stationary scenarios, the iSD method can significantly improve the channel availability and hence can enhance user QoE in bandwidth restricted IPTV delivery networks, with only slightly increasing the average service delay of channel enhancement layers.